Investigation and Design of High Efficiency Quadrature Power Amplifier for 5G Applications - Taha, Faris Hassan; Hussein, Shamil H.; Yaseen, Mohammed T.; Fadhil, Hilal A.; Assi, Saad A.; Desa, Hazry; Imran, Ahmed Imad; Radhi, Ahmed Dheyaa; Almulaisi, Taha (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
The rapid rise of the high data rate requirements in modern wireless communications, which include Wi-Fi, LTE, and 5G, demands that appropriate linear and efficient transmitter architecture gets designed. The increased power amplifier (PA) efficiency in the output power back-off (OPBO) is one of the major challenges because it is difficult to achieve PA power efficiency and linearity at the same time. The current study provides design and simulation of a Quadrature Power Amplifier (QPA) for application in 5G in the 5.8 GHz band using 120nm CMOS technology. The proposed QPA system combines Envelope Elimination and Restoration (EER) technique with direct I and Q signal modulation, quite a different solution from the “conventional” approaches of EER and represents very a bandwidth efficient one. Hard-switching drivers as well as the optimized matching networks are used by the system to ensure that there is high power transfer capability and low distortion. In the design process the source impedance is optimized using a source pull simulation and the load impedance is optimized by using a load pull simulation; then, the L-type network is designed to realize optimal matching. For use in implementation, the Rogers RO-5880 material is applied using transmission lines set up through the microstrip techniques in a bid to reduce the losses and parasitic ones. Simulation results show that the QPA obtains a peak output power of 24.35dBm and a power-added efficiency (PAE) of 70% at 5.8 GHz. The best input and output impedances were: and , respectively. In addition, the envelope and transient simulations prove high-accuracy signal transmission and clean switching quality. This QPA design offers a power-efficient solution with better performance characteristics that makes it an attractive candidate for the future 5G communication systems that are to operate in the 5.8 GHz frequency band.